2012
DOI: 10.1002/hipo.22063
|View full text |Cite
|
Sign up to set email alerts
|

The effects of combined perirhinal and postrhinal damage on complex discrimination tasks

Abstract: Rats with combined lesions of the perirhinal and postrhinal cortices were trained on a complex discrimination task, the simultaneous feature-positive and feature-negative discrimination task. In this task, a panel light (L) paired with an auditory stimulus determined whether a tone (T) or white noise (N) would be rewarded (+) or not rewarded (−). Thus, the light feature determined whether the target auditory stimuli were rewarded or not. In each session, trial types were LT+, T−, N+, and LN−. We had hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Our model would predict that manipulations of POR would not impair the formation of associations between sensory stimuli. Consistent with this, a recent study by Gastelum et al (2012) demonstrated that lesions involving POR did not impair (and in fact enhanced) the formation of associations between stimuli in a feature-positive feature-negative discrimination task. Additional studies such as these are essential in order to fully test the predicted dissociations predicated by a functional model.…”
Section: Avenues For Future Studysupporting
confidence: 67%
“…Our model would predict that manipulations of POR would not impair the formation of associations between sensory stimuli. Consistent with this, a recent study by Gastelum et al (2012) demonstrated that lesions involving POR did not impair (and in fact enhanced) the formation of associations between stimuli in a feature-positive feature-negative discrimination task. Additional studies such as these are essential in order to fully test the predicted dissociations predicated by a functional model.…”
Section: Avenues For Future Studysupporting
confidence: 67%
“…As such, POR is likely to reflect and integrate aspects of each network. For example, POR likely serves as a relay of visual object information to hippocampus, as lesion studies have implicated POR in object recognition, object learning, and object-directed orienting (Bussey et al, 2003; Davies et al, 2007; Gastelum et al, 2012). The few physiology studies that have recorded from identified POR (Burwell and Hafeman, 2003; Furtak et al, 2012) or nearby lateral cortical areas in rats (Vermaercke et al, 2014) are consistent with this notion.…”
Section: Discussionmentioning
confidence: 99%
“…PRh activity is associated with learning and mnemonic processing, and PRh lesions disrupt learned behaviors that involve auditory cues in rodents (Bang & Brown, ; Corodimas & LeDoux, ; Gastelum, Guilhardi, & Burwell, ; Lindquist et al, ; Plakke, Freeman, & Poremba, ; Robinson, Whitt, Horsley, & Jones, ; Sacchetti et al, ). For example, PRh lesions can interfere with learning a task in which visual features determine whether target auditory stimuli are rewarded (Gastelum et al, ). A role for e‐LTP during learning is supported by the observations that PRh neurons become more responsive to an auditory stimulus following conditioning (Furtak, Allen, & Brown, ) or the presentation of a familiar visual stimulus (von Linstow Roloff, Muller, & Brown, ).…”
Section: Introductionmentioning
confidence: 99%